A price for peace: troop contributing countries' responses to peacekeeper fatalities. Issue 6 (2nd November 2021) - Oestman, Jared
ABSTRACT: How do states respond to fatalities of their troops in UN peacekeeping operations (PKOs)? Recent research highlights that participation in peacekeeping is costly for most states. Personnel fatalities should create further costs for contributors and often result in a reduction of their commitments. Studies that evaluate this expectation yield mixed findings. One finds no evidence that OECD countries provide fewer personnel to UN PKOs following fatalities. In contrast, another finds that fatalities generally correspond with reductions in states' personnel commitments to UN operations in Africa but also reveals that wealthier contributors tend to withdraw at larger magnitudes than their poorer counterparts. This study builds on this work by further hypothesizing that the incentives that motivate states to participate in PKOs condition their willingness to maintain their contributions after experiencing fatalities. An analysis of states' troop fatalities and commitments to 41 UN operations from 1990 to 2015 supports this expectation. States that are contiguous to an operation, which face greater concerns about the externalities of nearby conflicts, and states that receive side payments for their troop commitments, via foreign aid, are more willing to maintain their commitments in response to fatalities of their troops than other contributors. Additional findings suggest that non-contiguous contributors that do not receive side payments are also inclined to withdraw troops in response to upticks in organized violence surrounding a mission as well as fatalities of other contributors' troops. These results illustrate that the motives that states face to participate in PKOs also affect their willingness to maintain their troop commitments as their costs for participation increase.